Blind pouch and blind handle (blind loop) symptomatic jejunal: In patients with old hepaticojejunostomies for iatrogenic lesions of the bile ducts - Ramos, Edgardo; Montano, Daniel; Cilleruelo, Roberto; Praderi, Raúl (Cirugía del Uruguay, 1994)
The blind pouch is formed in the distal stump of the proximal anse when a latero-lateral anastomosis is performed and that end remains too long. lt is of late appearance as is the case of the patient who had been operated six years befare. The vomiting that evacuated the pouch once a week ceased after resection. The blind loop appears when the surgeon makes a mistake when carrying out a Roux diverticular ansa and uses the proximal ansa with ascending perstaltism. In the case mentioned by the authors, the patient suffered from post-prandial cholangitis, as food refluxed to the biliar viae.